Enabling code transformations with FermaT on simplified bytecode. Issue 5 (20th February 2017) - Pracner, Doni; Budimac, Zoran
Abstract: This paper presents a new approach for working with Java bytecode that uses existing tools (FermaT and the wide spectrum language) that have been industrially tested and proven in transforming legacy assembly code. The first step has been a successful translator that works with a subset language (MicroJava) and enables the usage of formal transformations in FermaT to restructure the code from a machine level to human readable high level structures, both automatically and manually. It mostly relies on the existing transformations, but some new ones were introduced in this work, and some old ones were modified. Abstract : This paper presents a new approach for working with Java bytecode that uses existing tools (FermaT and the wide spectrum language) that have been industrially tested and proven in transforming legacy assembly code. The first step has been a successful translator that works with a subset language (MicroJava) and enables the usage of formal transformations in FermaT to restructure the code from a machine level to human readable high‐level structures, both automatically and manually. It mostly relies on the existing transformations, but some new ones were introduced in this work, and some old ones were modified.